2019
DOI: 10.1002/jcp.28752
|View full text |Cite
|
Sign up to set email alerts
|

Long noncoding RNA FOXD3‐AS1 promotes colon adenocarcinoma progression and functions as a competing endogenous RNA to regulate SIRT1 by sponging miR‐135a‐5p

Abstract: More and more documents have proved that the abnormal expression of long noncoding RNAs (lncRNAs) are correlated with the initiation and progression of colorectal cancer (CRC). lncRNA FOXD3-AS1 has been reported in glioma for its oncogenic property. According to the survival analysis of The Cancer Genome Atlas database, FOXD3-AS1 upregulation implied lower survival rate of patients with CRC. Quantitative real-time polymerase chain reaction showed the overexpression of FOXD3-AS1 in both CRC tissues and cells. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
39
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(41 citation statements)
references
References 39 publications
2
39
0
Order By: Relevance
“…For instance, Zhang et al demonstrated that miR‐135a could accelerate cell growth and proliferation of lung cancer, but repress cell apoptosis . In colon adenocarcinoma, miR‐135a was suggested to be a "sponge" of lncRNA FOXD3‐AS1 to regulate cell proliferation, migration, invasion, and apoptosis by targeting SIRT1 . In addition, several studies have also revealed that the positive effects of miR‐135a on BC cell proliferation, epithelial‐mesenchymal transition, migration and invasion .…”
Section: Discussionmentioning
confidence: 99%
“…For instance, Zhang et al demonstrated that miR‐135a could accelerate cell growth and proliferation of lung cancer, but repress cell apoptosis . In colon adenocarcinoma, miR‐135a was suggested to be a "sponge" of lncRNA FOXD3‐AS1 to regulate cell proliferation, migration, invasion, and apoptosis by targeting SIRT1 . In addition, several studies have also revealed that the positive effects of miR‐135a on BC cell proliferation, epithelial‐mesenchymal transition, migration and invasion .…”
Section: Discussionmentioning
confidence: 99%
“…FOXD3-AS1 was abundantly expressed in both colorectal cancer (CRC) tissues and cells, FOXD3-AS1 overexpression was associated with worse clinical outcomes of CRC patients. In addition, silence of FOXD3-AS1 was effective in suppressing CRC cell progression [ 15 ]. In this study, we first showed that FOXD3-AS1 was up-regulated in A549/DDP and H1229/DDP cells compared to their corresponding parental NSCLC cells.…”
Section: Discussionmentioning
confidence: 99%
“…LncRNA EGFR antisense RNA 1 (EGFR-AS1) was found to be elevated in plasma of NSCLC patients and EGFR-AS1 overexpression promoted cisplatin resistance in NSCLC [ 11 ]. Recent evidence implied that lncRNA FOXD3 antisense RNA1 (FOXD3-AS1) was involved in the progression of different malignancies [ 12 – 15 ]. Unfortunately, little is known about FOXD3-AS1 regarding chemo-resistance in NSCLC.…”
Section: Introductionmentioning
confidence: 99%
“…miR-135a and miR-9 are known to target SIRT1 expression 37 . Several studies have indicated that SIRT1 protects against stress-related diseases by interacting with p53, forkhead box protein (FOXO), NFκB and peroxisome proliferator-activated receptor gamma coactivator 1-alpha (PGC-1α), which regulate diverse cellular processes, including stress responses and inflammation 56,57 . In addition, the expression level of miR-25 increased in serum and lesion samples from vitiligo patients 47 .…”
Section: Mirnas Associated With Oxidative Stress In Vitiligomentioning
confidence: 99%